2017
DOI: 10.1542/peds.2016-1688
|View full text |Cite
|
Sign up to set email alerts
|

A Family-Centered Rounds Checklist, Family Engagement, and Patient Safety: A Randomized Trial

Abstract: The performance of FCR checklist elements was enhanced by checklist implementation and associated with changes in family engagement and more positive perceptions of safety climate. Implementing the checklist improves delivery of FCRs, impacting quality and safety of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 49 publications
1
85
1
4
Order By: Relevance
“…Intentionally involving parents and caregivers in the decision-making process (eg, through family centered rounds that begin by focusing on addressing parental concerns) is known to reduce medical errors and improve outcomes. 14…”
Section: Discussionmentioning
confidence: 99%
“…Intentionally involving parents and caregivers in the decision-making process (eg, through family centered rounds that begin by focusing on addressing parental concerns) is known to reduce medical errors and improve outcomes. 14…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the Patient Report and Action for a Safe Environment (PRASE) cluster randomized controlled trial found that surveying inpatients about their safety experiences had no impact on a global measure of safety [13]. Interventions in the form of checklists for bedside family-centered rounds for hospitalized children, enable parents to engage at all aspects of the care plan, improve the quality of care, and improve the patient safety from the parents' perspectives [15]. Notably, the OpenNotes project was demonstrated to help engage patients as safety partners without apparent negative consequences for clinician workflow or patient-clinician relationships [16].…”
Section: Reviewmentioning
confidence: 99%
“…23 Checklists can also be useful cognitive aids to facilitate an encounter and manage the cognitive load of learners. 24 Ultimately, hesitancies can be overcome with experience.…”
Section: What We Should Do Insteadmentioning
confidence: 99%